ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH (eWOM) DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN BERKUNJUNG KE AGROWISATA KAMPOENG ANGGREK KEDIRI - Romadhoni, Arif; Nugroho, Sigit Dwi; Sudiyarto, Sudiyarto (Berkala Ilmiah AGRIDEVINA, 2021)
The purpose of this study are: 1) Describe the characteristics of visitors to the Kampoeng Anggrek Kediri Agro-tourism. 2) Analyzing the influence of Electronic Word Of Mouth (eWOM) on the decision to visit Kampoeng Anggrek Kediri Agro-Tourism. 3) Analyzing the effect of service quality on the decision to visit the Kampoeng Anggrek Kediri Agro-tourism. The research method was done intentionally (purposive) with a purposive sampling of 50 people. Research testing is done by studying the Structural Equation Model (SEM) software based on WarpPLS 5.0 Partial Least Square (PLS). The results of this study show the characteristics of Kampoeng Anggrek Kediri Agro-tourism visitors based on gender that is equal between men and women, dominant visitors get 21-30 years obtained from Kediri. Education visitors gather high school status as students, and the level of income between Rp. 0-500,000. The first visit was to the Kampoeng Anggrek Kediri Agro-tourism and a personal visit using a type of motorcycle transportation. The word of mouth electronic variable (eWOM) (X1) has a positive effect on the visit decision variable. service quality variables were significantly positive for visit decision variables. DOI : https://doi.org/10.33005/adv.v10i1.2615